The Textual History of the Bible from the Dead Sea Scrolls to the Biblical Manuscripts of the Vienna Papyrus Collection : Proceedings of the Fifteenth International Symposium of the Orion Center for the Study of the Dead Sea Scrolls and Associated Literature, Cosponsored by the University of Vienna Institute for Jewish Studies and the Schechter Institute of Jewish Studies - Clements, Ruth A., (Studies on the Texts of the Desert of Judah ;, 2022)
Biblical manuscripts from the Dead Sea and the Cairo Genizah have added immeasurably to our knowledge of the textual history of the Hebrew Bible. The papers collected in this volume compare the evidence of the biblical DSS with manuscripts from the Vienna Papyrus Collection, connected with the Cairo Genizah, as well as late ancient evidence from diverse contexts. The resulting picture is one of a dialectic between textual plurality and fixity: the eventual dominance of the consonantal Masoretic Text over the textual plurality of the Second Temple period, and the secondary diversification of that standardized text through scribal activity.